SHARIA BANK SERVICE MARKETING MANAGEMENT STRATEGY IN INDONESIA - Adinda Cahya Maharani; Muhammad Iqbal Fasa; Suharto suharto (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2022)
Indonesia, which is predominantly Muslim, has long wanted a system of financial institutions that is in line with the demands of not limited financial needs but also moral demands. Islamic banks function as a collection of funds from the public in the form of savings must be based on Sharia principles. With the passage of time, the dynamics of Islamic bank players in marketing sales of products and services that are increasingly high, of course, make Islamic Banks required to have a strategy to compete competitively. Because Marketing strategy has a function as an organization and a set of processes in creating, communicating and submitting assessments to consumers in managing good relations with consumers which is carried out in a way that can provide benefits to the organization and its owners. The type of research used is literature study. The result of the research is that the marketing strategy of Islamic banking services is a strategy to serve the market or market segment that can be used as a target by an entrepreneur. The strategy of Islamic banking services can be carried out using segmentation, targeting and positioning strategies. Therefore, a good service system in Islamic banks is very necessary. Indonesia yang mayoritasnya beragama Islam telah lama mendambakan kehadiran sistem lembaga keuangan yang sesuai dengan tuntutan kebutuhan tidak terbatas finansial namun juga tuntutan moralitasnya. Bank syariah berfungsi sebagai penghimpunan dana dari masyarakat dalam bentuk tabungan harus berprinsip Syariah. Dengan berjalannya waktu dinamika pelaku bank syariah dalam memasarkan penjualan produk dan jasa yang semakin tinggi tentunya membuat Bank Syariah diharuskan mempunyai strategi untuk bersaing secara kompetitif. Dikarenakan strategi pemasaran memiliki fungsi sebagai organisasi dan seperangkat proses dalam penciptaan pengkomunikasian dan penyerahan penilaian kepada konsumen dalam pengelolaan hubungan baik dengan konsumen yang dilakukan dengan cara yang dapat memberikan keuntungan bagi organisasi dan para pemiliknya. Jenis penelitian yang digunakan ialah studi pustaka. Hasil penelitian adalah strategi pemasaran jasa bank syariah ialah strategi untuk melayani pasar atau segmen pasar yang dapat dijadikan sebagai target oleh seorang pengusaha.Strategi jasa bank syariah dapat dilakukan dengan menggunakan strategi segmentasi, target dan positioning. Oleh karena itu sistem pelayanan yang baik di bank syariah sangat diperlukan.